2008
DOI: 10.1007/s10350-007-9171-6
|View full text |Cite
|
Sign up to set email alerts
|

Ligasure™ Precise vs. Conventional Diathermy for Milligan-Morgan Hemorrhoidectomy: A Prospective, Randomized, Multicenter Trial

Abstract: Ligasure hemorrhoidectomy is an effective procedure for Grades III and IV hemorrhoids and facilitates a faster return to work and normal activities by reducing postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 19 publications
4
47
1
3
Order By: Relevance
“…The present study showed, as other studies have [10,[17][18][19], that after LH, return to work and normal activities was significantly faster than after conventional OH owing to reduced postoperative pain and faster wound healing. This, in addition to reduced operative time, may compensate for the higher cost of the LigaSure electrodes, particularly since reduced pain did not lead to a shorter hospital stay.…”
Section: Discussionsupporting
confidence: 66%
“…The present study showed, as other studies have [10,[17][18][19], that after LH, return to work and normal activities was significantly faster than after conventional OH owing to reduced postoperative pain and faster wound healing. This, in addition to reduced operative time, may compensate for the higher cost of the LigaSure electrodes, particularly since reduced pain did not lead to a shorter hospital stay.…”
Section: Discussionsupporting
confidence: 66%
“…1,3,4,6,[8][9][10][11][12][13][14][15][16][17][18] Anal/rectal stenosis observed was about five times higher in EH group in spite of leaving islands of normal skin and mucosa to avoid stricture formation, which was managed conservatively. Recurrence, residual skin tags and prolapse were observed to be three times higher in SH group, comparable results were observed by Yang J et al [1][2][3][4][5] …”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve risk prediction on a patient level it is necessary to understand the role and interplay of the factors which increase the risk of, or provide protection against, POUR. Within ambulatory general surgery, several risk factors have been established relating to operative factors (including equipment and technique [5][6][7][8][9][10][11][12] ) and anaesthetic factors (including intravenous fluid use and route of anaesthesia [13][14][15][16][17][18][19][20][21][22][23] ). However there is a paucity of work on the influence of patient-related factors.…”
Section: Introductionmentioning
confidence: 99%